2015
DOI: 10.1111/jsm.12835
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Satisfaction and Distress in Sexual Functioning in a Sample of the BDSM Community: A Comparison Study Between BDSM and Non-BDSM Contexts

Abstract: Introduction Little attention has been paid to distress in sexual functioning or the sexual satisfaction of people who practice BDSM (Bondage and Discipline, Domination and Submission, Sadism and Masochism). Aim The purpose of this study was to describe sociodemographic characteristics and BDSM practices and compare BDSM practitioners' sexual outcomes (in BDSM and non-BDSM contexts). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 30 publications
1
19
0
2
Order By: Relevance
“…A recent interview-based study 83 showed that a small sample (n = 32) of practitioners indicated that their sexual BDSM experiences were primarily emotional and psychological in nature and that these were preferred over mainstream (“vanilla”) sexual interactions. In contrast, Pascoal’s small-scale survey study (n = 68) 84 revealed that BDSM and non-BDSM sexual activities were experienced as equally satisfying and that most practitioners did not exclusively engage in BDSM-oriented sexual practices. Nevertheless, they accentuate how BDSM-themed sexual interactions deepen the interpersonal connection more than non-BDSM sexuality.…”
Section: Resultsmentioning
confidence: 86%
“…A recent interview-based study 83 showed that a small sample (n = 32) of practitioners indicated that their sexual BDSM experiences were primarily emotional and psychological in nature and that these were preferred over mainstream (“vanilla”) sexual interactions. In contrast, Pascoal’s small-scale survey study (n = 68) 84 revealed that BDSM and non-BDSM sexual activities were experienced as equally satisfying and that most practitioners did not exclusively engage in BDSM-oriented sexual practices. Nevertheless, they accentuate how BDSM-themed sexual interactions deepen the interpersonal connection more than non-BDSM sexuality.…”
Section: Resultsmentioning
confidence: 86%
“…A similar argument can be made in the case of submission and bondage. In fact, bondage forms of sex may be as satisfying as a more regular practice (Pascoal et al, 2015). Another point is that women may appreciate (mock) rape because it offers an experience of being considered particularly attractive (Hazen, 1983).…”
Section: Sexual Preferencesmentioning
confidence: 99%
“…For example, discussions over pain with sexual intercourse [1] and the role of testosterone in female sexual desire [2] have received special interest in scientific circles. Meanwhile a study on real life “Bondage and Discipline, Domination and Submission, Sadism and Masochism” gained wide popular interest after the release of blockbuster movie Fifty Shades of Grey and recently a study an women's perception of penile appearance has caught the attention of the public [3,4]. As of September 2015, @JSexMed has 905 “likes” on Facebook and more than 1,500 followers on Twitter.…”
Section: Upcoming Conferences To Be Covered By @Jsexmedmentioning
confidence: 99%